Monitoring Sustainable Development Goals 3: Assessing the Readiness of Low- and Middle-Income Countries - Nabukalu, Joy Belinda (Int J Health Policy Manag, 2019)
Background: The Millennium Development Goals (MDGs) availed opportunities for scaling up service coverage but called for stringent monitoring and evaluation (M&E) focusing mainly on MDG related programs. The Sustainable Development Goals 3 (SDGs) and the universal health coverage (UHC) agenda present a broader scope and require more sophisticated M&E systems. We assessed the readiness of low- and middle-income countries to monitor SDG 3. Methods: Employing mixed methods, we reviewed health sector M&E plans of 6 countries in the World Health Organization (WHO) Africa Region to assess the challenges to M&E, the indicator selection pattern and the extent of multisectoral collaboration. Qualitative data were analysed using content thematic analysis while quantitative data were analysed using Excel. Results: Challenges to monitoring SDG 3 include weak institutional capacity; fragmentation of M&E functions; inadequate domestic financing; inadequate data availability, dissemination and utilization of M&E products. The total number of indictors in the reviewed plans varied from 38 for Zimbabwe to 235 for Zanzibar. Sixty-nine percent of indicators for the Gambia and 89% for Zanzibar were not classified in any domain in the M&E results chain. Countries lay greater M&E emphasis on service delivery, health systems, maternal and child health as well as communicable diseases with a seeming neglect of the non-communicable diseases (NCDs). Inclusion of SDG 3 indicators only ranged from 48% for Zanzibar to 67% for Kenya. Although monitoring SDG 3 calls for multisectoral collaboration, consideration of the role of other sectors in the M&E plans was either absent or limited to the statistical departments. Conclusion: There are common challenges confronting M&E at county-level. Countries have omitted key indicators for monitoring components of the SDG 3 targets especially those on NCDs and injuries. The role of other sectors in monitoring SDG 3 targets is not adequately reflected. These could be bottlenecks to tracking progress towards SDG 3 if not addressed. Beyond providing compendium of indicators to guide countries, we advocate for a more binding minimum set of indicators for all countries to which they may add depending on their context. Ministries of Health (MoHs) should prioritise M&E as an important pillar for health service planning and implementation and not as an add-on activity.